Fabrication of porous polyaniline modified MWNTs core-shell structure for high performance supercapacitors with high rate capability. (5th August 2017) - Du, Pengcheng; Lin, Lu; Wang, Hongxing; Liu, Dong; Wei, Wenli; Li, Jiagen; Liu, Peng
Abstract: Novel porous polyaniline (PANI) modified MWNTs core-shell structure materials (porous CNTs-PANI) were fabricated by in situ polymerization using the "worm-like" MnO2 modified MWNTs (CNTs-MnO2 ) as the reactive template. The MnO2 layer on surface of MWNTs can act as the reactive template in the polymerization process. Meanwhile, the reactive etching of the MnO2 can form porous structure of PANI for fabrication of porous CNTs-PANI core-shell structure, which exhibits outstanding electrochemical performance among the CNTs-PANI and pure PANI materials. The porous CNTs-PANI materials possess an excellent specific capacitance of 406.5 F/g at 0.5 A/g, exhibit good rate capability of 84.7% even up to 50 A/g, and keep 72% of its original value up to 1000 charge-discharge cycles at the current density of 10 A/g, also maintain 55% capacitance retention at 2200 charge-discharge cycles. Furthermore, the porous CNTs-PANI materials exhibit an extremely high energy density of 55.6 Wh/kg at the power density of 0.25 kW/kg. The novel porous CNTs-PANI core-shell structure materials reveal promising applications in high performance supercapacitors. Graphical abstract: Highlights: Novel porous PANI modified MWNTs core-shell material (porous CNTs-PANI) was fabricated. The porous CNTs-PANI possesses an excellent specific capacitance of 406.5 F/g at 0.5 A/g. It exhibits good rate capability of 84.7% even up to 50 A/g. It exhibits a high energy density of 55.6 Wh/kg at the power density of 0.25 kW/kg.